GENEALOGI DAN JEJARING LEMBAGA PENDIDIKAN ISLAM INDONESIA DENGAN LEMBAGA PENDIDIKAN ISLAM DUNIA: SEJARAH, PENGARUH, DAN DINAMIKA GLOBAL - Maghfirotun Chasanah; Moh.Roqib (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Islamic Education in Indonesia has developed through interactions with centers of Islamic scholarship worldwide, ranging from traditional pesantren to madrasahs and Islamic universities. This study employs a literature review method with content and historical analysis to trace the genealogy of Islamic education, its development, and its contribution to global dynamics. The findings reveal that Islamic education in Indonesia has undergone three major phases: first, the formation of pesantren influenced by Islamic scholarly traditions from the Middle East and South Asia; second, the modernization of madrasahs, which adapted formal education systems in response to colonialism and contemporary demands; and third, the globalization of Islamic education, marked by academic cooperation, student exchanges, and the influence of Islamic thought from various parts of the world. The network of Islamic education in Indonesia continues to expand through increased intellectual mobility, curriculum enhancement that integrates religious and scientific knowledge, and adaptation to global challenges. By understanding historical patterns and global dynamics, Islamic educational institutions in Indonesia can continue to contribute to strengthening Islamic civilization on a broader scale.